2020
DOI: 10.1109/access.2020.2983300
|View full text |Cite
|
Sign up to set email alerts
|

A Secure AI-Driven Architecture for Automated Insurance Systems: Fraud Detection and Risk Measurement

Abstract: The private insurance sector is recognized as one of the fastest-growing industries. This rapid growth has fueled incredible transformations over the past decade. Nowadays, there exist insurance products for most high-value assets such as vehicles, jewellery, health/life, and homes. Insurance companies are at the forefront in adopting cutting-edge operations, processes, and mathematical models to maximize profit whilst servicing their customers claims. Traditional methods that are exclusively based on human-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(45 citation statements)
references
References 37 publications
0
30
0
Order By: Relevance
“…Futuristically, several existing breakthroughs in computing like Cloud Computing [18], Internet of Things (IoT) [59], Artificial Intelligence (AI), machine learning methods [60], and data analytics [61] will be joined and leveraged to automate and drastically transform the manner in which insurance processes are handled contemporarily. The following are the major types of insurance being provided by modern companies and how blockchain's contribution can be implemented.…”
Section: A Major Types Of Insurancementioning
confidence: 99%
“…Futuristically, several existing breakthroughs in computing like Cloud Computing [18], Internet of Things (IoT) [59], Artificial Intelligence (AI), machine learning methods [60], and data analytics [61] will be joined and leveraged to automate and drastically transform the manner in which insurance processes are handled contemporarily. The following are the major types of insurance being provided by modern companies and how blockchain's contribution can be implemented.…”
Section: A Major Types Of Insurancementioning
confidence: 99%
“…The design uses a combination of heuristic and predictive techniques to perform optimization for moving targets. An automated framework for insurance companies is suggested using an extreme gradient boosting algorithm on blockchain-based transactional records [5]. The results showed that XGboost produces high performance as compared to other existing learning algorithms.…”
Section: Related Workmentioning
confidence: 99%
“…The shape and scale parameters of gamma distributions are a and b respectively. The formula for Mean µ and standard deviation σ in terms of gamma distribution parameters are represented in Equations ( 4) and (5).…”
Section: Data Driven Analysis Using Probability Distribution Modelmentioning
confidence: 99%
“…The participants that are allowed to read or write to the ledger are called peers. Thus, it is easier to control the transactions on the ledger and it has higher system throughput [21][22][23]. Hyperledger Fabric secures the interactions among a group of authorized participants to preserve privacy and confidentiality [22].…”
Section: Hyperledger Composer and Hyperledger Fabricmentioning
confidence: 99%